Issues and paths forward in the identification and reuse of historic analog records - Anderson, Bethany G.; Antognoli, Erin; Caldrone, Sandi L.; Derner, Justin D.; Farrell, Shannon L.; Fenlon, Katrina; Hendrickson, John R.; Hendrickson, Lois G.; Johnson, Holly A.; Kaplan, Nicole E.; Kelly, Julia A.; Mastel, Kristen L.; et al. (Frontiers in Environmental Science, 2024)
Introduction: Historic data, often in analog format, is a valuable resource for assessing effects of directional changes in climate and climatic variability. However, historic data can be difficult to locate, interpret, and reformat into a useful state. Methods: Teams of scientists, librarians, archivists, and data managers at four US institutions have undertaken various projects to gather, describe, and in some cases, transform historic data. They have also surveyed researchers who either possess historic data or have used it in their work. Results: Historic data projects involved locating data, writing data descriptions, and connecting with individuals who had knowledge about the data’s collection. The surveys and interviews found that researchers valued historic data and were worried that it was at risk of loss. They noted the lack of best practices. Discussion: Each project attempting to rescue or enhance access to historic data has a unique path but being guided by FAIR principles should be at the core whether or not the end result is machine-readable data. Working with a team incorporating librarians, archivists, and data managers can aid individual researchers’ in producing accessible, and reusable datasets. There is much work to be done in raising awareness about the value of historic data but motivating factors for doing so include its usefulness in environmental research and other disciplines and its risk of loss as researchers retire and are unsure of how to save historic data, both in analog and electronic formats.